Scientometric Evaluation of Research Productivity on Diabetes from the Kingdom of Saudi Arabia over the Last Two Decades (2000-2019) - Zohair Jamil Gazzaz; Nadeem Shafique Butt; Nadeem Alam Zubairi; Ahmad Azam Malik (Journal of Diabetes Research)
Background and Objectives. Diabetes Mellitus (DM) is a leading global cause of morbidity and mortality with additional threats from known prevalent risk factors. Despite huge investments and increased publications, it is challenging to assess research output. Importantly, the literature on publication trends and performance evaluation is scarce from regions including the Kingdom of Saudi Arabia (KSA). This study is aimed at analyzing diabetes-related research output from KSA over the last two decades (2000-2019). Materials and Methods. Data was extracted from the Web of Science (WoS) platform and later bibliometric analysis performed using the “R-Bibliometrix” package. A wide range of indicators was explored to measure the quantity and quality of the publications related to diabetes from KSA. Results. Saudi Arabia was 28th in rank with 2600 documents (0.83% of global share). Articles were the main document type (76%). The total number of authors was 9715 from 104 countries. Three authors showed >50 publications and >100 total citations while 2 authors showed an H-index of ≥20. The USA, UK, and Egypt were other leading contributive countries in terms of corresponding authors and total citations per country. King Saud University was the major contributing affiliation followed by King Abdulaziz University. Among 865 sources, Saudi Medical Journal was the leading and consistent source over the years. Diabetes, Diabetes Mellitus, and Type 2 Diabetes were the most frequently used keywords. Conclusion. This study provides a macroscopic overview of diabetes-related research output from KSA. Overall, similar identifications and trends of top authors were observed in terms of productivity, impact, international collaborations, and organizational affiliations. Generally, an increasing productivity trend was observed with the majority published in the last 5 to 10 years. Study findings can benefit relevant stakeholders to better understand the trends and performance of diabetes-related regional research.